The Influence of Managerial Ability of School Principals and The Climate of School Organizations on Teacher Performance During The Covid-19 Pandemic - E, Khuluqo I; M, Tenkahary C (Journal of Education Technology, 2021)
The role of school principals is very important in optimizing teacher performance during the Covid-19 pandemic. In addition, a conducive school organizational climate is able to provide solutions to teacher performance problems that arise during the Covid-19 pandemic. This study aims to analyze the effect of Principal Managerial Ability and School Organizational Climate on Teacher Performance During the Covid-19 Pandemic. This type of research is quantitative research. The research method used is a quantitative method. The population in this study amounted to 184. The sample in this study was 126 teachers. The technique used to collect data is interview and observation. The instrument used to collect data is a questionnaire. The results showed that the principal's managerial ability had an effect on teacher performance as indicated by the Fcount 92,102 (p <0.05) and had a strong tightness based on the correlation coefficient value of 0.653. Furthermore, the school organizational climate affects teacher performance as indicated by the Fcount 126,784 (p <0.05) and has a strong tightness based on the correlation coefficient of 0.711. In addition, the principal's managerial ability and school organizational climate simultaneously affect teacher performance based on the Fcount 75.497 (p <0.05) and has a strong tightness based on the R value of 0.742. It can be concluded that the principal's managerial ability and the school's organizational climate simultaneously affect teacher performance during the Covid-19 pandemic.